Optimalisasi Potensi Pajak dan Retribusi Daerah dalam Rangka Meningkatkan Pendapatan Asli Daerah di Kabupaten Ende - B. Wahab Thalib, Sabra; D. Gadi Djou, Laurentius; Leha, Ernesta (E-Jurnal Akuntansi; Vol 30 No 10 (2020)DO - 10.24843/EJA.2020.v30.i10.p18, 2020)
The purpose of this research is to analyze the contribution, effectiveness and efficiency of taxes and retribution on PAD. To analize public perceptions and constraints in the system of collecting taxes and retribution in Ende district. To formulate policy strategies in optimizing local tax and retribution revenues in Ende district. This research is a quantitative research and the sampling technique uses purposive sampling. The population used is all DPPKAD apparatus, related agencies, tax and retribution payers in Ende regency. The results showed that the contribution of taxes and retribution is at a moderate level and is quite good. Effectiveness of taxes and retributions are classified as less effective and very effective. Efficiency of taxes and retribution is in an efficient position. Meanwhile, the obstacles faced in the context of local taxes and retribution in Ende regency are the lack of a base for taxes and retribution managed by the regions. Keywords: PAD Optimalization; Tax; Retribution.